From heartbroken wives to working mothers : the Malay melodrama of the early 1980s / Norman Yusoff - Yusoff, Norman (UPENA, 2006)
This essay examines the Malay melodrama produced in the early 1980s by focusing upon the representation and (re)construction of gender and its extent to which the genre subverts its conventionality in relation to the gender subjectivity and relativity. Since cinematic texts, as forms of representation, are polysemic, my argument is that the depiction of women in the melodramas does not perpetuate them as "commodified" and stereotyped into the binary images of "good" and "bad" due to the films' renegotiation of the ambiguities of representation. On the other hand, the portrayal of men, which seems negative, resonates in ways that contest and question their masculinity. My analysis will go on to trace the social, economic and political implications in Malaysia during the early 1980s as the country was on the verge of modernization and how they reflect and shape the defining features of the Malay melodrama of the early 1980s. In a way, the essay aims to map and frame the notion of genres "as a form of collective cultural expression" (Schatz, 1981), by underlining the socio-cultural and ideological functions which the Malay melodrama of the early 1980s performs.